Intake Patterns of Essential Amino Acids in Latin America: Results from the ELANS Study - Herrera Cuenca, Marianella (2023)
Background Traditionally, nutrition epidemiological studies have analyzed the intake of each amino acid (AA) separately. Essential AA are key components of the human diet because the body cannot synthesize them. In order to study the complex interaction between AA and food in the diet, this study aimed to identify and analyze the intake pattern of essential AA through foods in ELANS countries. Methodology The ELANS was a Cross-sectional, multicenter study conducted in Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru, and Venezuela; in both sex adolescents and adults aged 15–65 years. Food and beverage consumption was recorded during two non-consecutive household visits using 24-hour recall. The Nutrition Data System for Research transformed this intake into AA values. The final sample comprised 9218 individuals, of whom 6648 were considered plausible reporters. Principal Component Analysis (PCA) was performed to obtain the AA intake patterns, and non-parametric tests were used to identify patterns by food group. Results Less than 8% of study participants had a deficient intake of essential AA (mg/kg/d). Ecuador had the highest AA intake, while Costa Rica and Chile had the lowest. Ecuador and Peru stand out for a high consumption of tryptophan (mean:13.1; std.err.:0.12), which is related to the high consumption of poultry and fish, while Brazil, Colombia, and Argentina reported high consumption of lysine (mean:77.8; std.err.:0.62) and histidine (mean:31.6; std.err.:0.24) aligned with high consumption of beef and pork. Conclusions The pattern of essential AA intake between countries differed according to the type of animal food source.